PELAKSANAAN FUNGSI PENGAWASAN UPT P4OP DINAS PENDIDIKAN PADA PROGRAM KARTU JAKARTA PINTAR DI DKI JAKARTA - Idrus, Iqbal Aidar; Sahdiyah, Nur Halimah Tun (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2020)
This study aims to analyze the implementation of the Supervision Function in the Jakarta Smart Card Program which is carried out by the UPT P4OP Education Office in the Jakarta Smart Card program in DKI Jakarta. Researchers used a supervisory approach which consisted of two surveillance techniques: direct supervision and indirect supervision. Direct supervision has three aspects: direct inspection, direct reporting, and direct observation. Meanwhile, indirect supervision has two aspects: oral reports and written reports. This research use desciptive qualitative approach. The results showed that the supervision of the UPT P4OP DKI Jakarta Provincial Education Office in monitoring the implementation of the Jakarta Smart Card program, where direct supervision has three aspects, namely direct inspection, on-site observation and on-site reports in these three aspects the supervision carried out by P4OP has been carried out optimally in accordance with the applicable provisions, while indirect supervision consists of two aspects, namely oral reports and written reports that have been running well, however, in the use of KJP funds it is still used for purposes outside the student's school, so the task of the UPT and the school must maximize supervision in the use of KJP funds used by students or parents of these students as input for the UPT P4OP DKI Provincial Education Office. Jakarta and Education Units in DKI Jakarta or schools related to the implementation of the KJP program in DKI Jakarta Province.